Morphodynamical modelling of field-scale swash events - Incelli, Giorgio; Dodd, Nicholas; Blenkinsopp, Chris E.; Zhu, Fangfang; Briganti, Riccardo (Elsevier, 2016)
In the present work, data for three single swash events are selected from those available for an accretive tide that occurred at Le Truc Vert beach (France) during a measurement field campaign at that location. These events are primarily chosen because of the different final bed change they produced, namely variable accretion, seaward erosion/landward deposition and variable erosion along the swash zone. These data are compared to results obtained from a ‘state-of-the-art’ numerical fully-coupled 1D morphodynamical shallow water solver, driven by measurements made of those events in the lower swash/inner surf zone.